The Dark Personality in a Sample of Adults: A Theoretical and Psychometric Study - Al Farhan, Ali Abdullah; Nasser, Kholoud Khaled; Alqahtani , Fahad Omair (Journal of Ecohumanism, 2025)
This study evaluates the psychometric properties of the Dark Triad Scale within a Saudi Arabian context. A total of 205 participants were involved, with a mean age of 34.48 years (SD = 8.57). Exploratory factor analysis identified a three-factor structure corresponding to Machiavellianism, narcissism, and psychopathy, each exhibiting high internal consistency (Cronbach’s α = 0.92 for Machiavellianism, α = 0.91 for narcissism, and α = 0.89 for psychopathy). The factors demonstrated satisfactory composite reliability (CR > 0.70) and acceptable convergent and discriminant validity, as indicated by an average variance extracted (AVE) greater than 0.50. Measurement invariance across gender was also established. These results suggest that the Saudi version of the Dark Triad Scale is a valid and reliable instrument for assessing the darker aspects of personality in this cultural context.